THE INFLUENCE OF INTERPERSONAL COMMUNICATION AND PRODUCT QUALITY TO THE CUSTOMERS SATISFACTION AT BRI UNIT SAM RATULANGI UNIVERSITY - Onggeleng, Edward Bernhard; Jorie, Rotinsulu Jopie (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
The bank enhances it’s value to customer’s by conducting interpersonal communication between namely providing transparant information to customer’s and serve any complaint’s by service excellence. Increasing the value of may also be convened by producing superior productj an easy process and give  advantage’s which are expected by customers. Through good interpersonal communication and product quality it is expected that customers will be satisfied. This research aims to understand the influence of interpersonal communication and product quality to customer satisfaction BRI Unit UNSRAT. This research uses survey, with the associative research method. The multiple linear regression analysis techniques is used. The results of the research, are significantly interpersonal communication and product quality simultaneously influences customer satisfaction. Partialy interpersonal communication influences customers satisfaction, while product quality does not significantly influence customer satisfaction at BRI Unit UNSRAT. Since interpersonal communication have a significant positive influence it will provide significant contributions to customer satisfaction at BRI Unit Unsrat. Therefore BRI  should pay attention to interpersonal communication and improve the product quality offered to customers. Keywords: interpersonal communication, product quality, customer satisfaction